Modern Bacterial Taxonomy - Austin Brian; Priest Fergus (Van Nostrand Reinhold, 1986)
The text comprises eight chapters, dealing with classification, numerical taxonomy, chemosystematics and molecular biology, phylogenetics, nomenclature, identification, the interaction between taxonomy and allied subjects (namely biotechnology, culture collections, ecology, genetics and pathology) and a final ''outlook'' chapter. Preface, Introduction, Classification, Numerical Taxonomy, Chemosystematics and Molecular Biology, Phylogenetics, Nomenclature, Identification and Diagnosis, Interactions Between Taxonomy and Allied Disciplines, Conclusions and Outlook, Glossary, Appendix 1: Classification of Bacteria, Index.